Assessing the Potential of Water Reuse Uptake Through a Private–Public Partnership: a Practitioner's Perspective - Isabella Georgiou; Serena Caucci; Jonathan Clive Morris; Edeltraud Guenther; Peter Krebs (Circular Economy and Sustainability, 2022)
Around 20% of the global water abstractions are originated by the industrial sector, while water demand overall will increase by 20–33% by 2050. Wastewater could provide an alternative source of water for industrial activities. There are not many studies exploring the potential of treated wastewater use under a private–public partnership (PPP), despite their potential of contributing to an effective integrated water management through the creation of inter-sectorial synergies. This paper aims therefore to provide a holistic overview of the main factors that affect the effectiveness of PPPs in using treated municipal wastewater in the industrial sector. Through a systematic literature review, the main barriers, drivers, industries and different applications of water use are analysed. Barriers and drivers are classified through the inductive Gioia method into seven categories. The results showed that economic and technical aspects related to the feasibility of the scheme were most prominent in the literature, while water availability seems to be central driving factor for such water reuse schemes. The conclusion of PPPs in water reuse, however, relies on the possibilities for such a partnership and on bridging the needs of the two parties, which entails effective communication through negotiation and information sharing. This paper is a first step to understanding how water circularity practices under an interconnected and sustainable urban environment can be facilitated and explored.
Keywords: 330; Systematic literature review; Industry; Implementation; Barriers; Drivers; Treated wastewater